Linking spatial patterns of groundwater table dynamics and streamflow generation processes in a small developed catchment - Orlowski, Natalie; Lauer, Florian; Kraft, Philipp; Frede, Hans-Georg; Breuer, Lutz; Justus Liebig University Giessen (My University, 2014)
Knowledge about water flow paths is essential for understanding biogeochemical fluxes in developed agricultural landscapes, i.e., the input of nutrients into surface waters, soil erosion, or pesticide fate. Several methods are available to study rainfall-runoff processes and flux partitioning: hydrometric based approaches, chemical tracers, modeling, and stable isotope applications. In this study a multi-method approach was conducted to gain insights into the hydrological fluxes and process understanding within the complex anthropogenic-influenced catchment of the Vollnkirchener Bach, Germany. Our results indicate that the catchment responds differently to precipitation input signals and dominant runoff-generation processes change throughout the year. Rainfall-induced runoff events during dry periods are characterized by a temporarily active combined sewer overflow. During stormflow, a large contribution of fast event water is observed. At low flow conditions losing and gaining conditions occur in parallel. However, when catchment´s moisture conditions are high, an ephemeral source from clay shale-graywacke dominated forested sites becomes active. The study reveals that the collection of detailed distributed hydrometric data combined with isotopic tracers, provides fundamental information on the complex catchment behavior, which can finally be utilized for conceptualizing water fluxes at a small catchment scale.
Keywords: groundwater-surface water interaction; groundwater table dynamics; multi-method approach; flow duration curve; lag-to-peak time; ddc:630